Re-Centring Periphery through Non-Co-Operation: Khwajasara Movement and Limits of Global Law in Pakistan - Hamzić, Vanja (2012)
This study presents a critical legal ethnography of Pakistani khwajasara, located at the very periphery of international law yet at the centre of global legal crisis. Khwajasara, known elsewhere as hijra, are Pakistani gender variant subject position, whose cultural memory and historical roots run deep into the region’s Mughal past (and beyond). This piece attempts to recount their long-lasting legal and political battle with Pakistani judicial system, against a backdrop of an important episode in their struggle – a 23 December 2009 judgment of the Supreme Court of Pakistan’s Chief Justice granting them a ‘third gender’ status on their respective identification cards – which is yet to be implemented. One of the paradigmatic facets of khwajasara, analysed here primarily as a political movement rather than an essentialised identitary script, is their decidedly counter-hegemonic approach, which has consistently declined even strategic co-operation with international legal (human rights) mechanisms, global (northern) LGBT movement, international organisations and even some instances of national governmental or civil society structures. This piece interrogates their radical politics of periphery as a phenomenon indicative of the limits of global governance project, inscribed in its insurmountable liberal and imperial nature. It calls for re-centring of resistance movements around the politics of non-participation, including in domestic legal battles.